2009
DOI: 10.1590/s0080-62342009000200020
|View full text |Cite
|
Sign up to set email alerts
|

A percepção de mulheres quanto à vulnerabilidade feminina para contrair DST/HIV

Abstract: Pesquisa descritiva com abordagem qualitativa cujo objetivo foi analisar a percepção de mulheres quanto à vulnerabilidade feminina para contrair DST/HIV. Foi realizada em 2006, num campus universitário no Rio de Janeiro. Foram entrevistadas 12 mulheres, de idade superior a 18 anos, de diferentes níveis de escolaridade, raça e religião. Estas eram estudantes, servidoras técnico-administrativas, docentes e outras usuárias. Foram atendidas as exigências do Conselho Nacional de Ética em Pesquisa. Os dados foram an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
42

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 8 publications
(14 reference statements)
0
31
0
42
Order By: Relevance
“…This index reaches levels similar to other international surveys conducted by the WHO 22,23 . By contrast, the presence of syphilis has been observed both in old age as well as in both sexes in some studies 24,25 . The authors hypothesize that pharmaceutical innovations have prolonged the sexual life of individuals, causing an increase in promiscuity mainly in men 24,25 .…”
Section: No Yes No Yesmentioning
confidence: 90%
See 1 more Smart Citation
“…This index reaches levels similar to other international surveys conducted by the WHO 22,23 . By contrast, the presence of syphilis has been observed both in old age as well as in both sexes in some studies 24,25 . The authors hypothesize that pharmaceutical innovations have prolonged the sexual life of individuals, causing an increase in promiscuity mainly in men 24,25 .…”
Section: No Yes No Yesmentioning
confidence: 90%
“…Marriage is highlighted as a protective factor against disease. Love, loyalty, respect, trust, and complicity create a romantic vision and can lead to the abandonment of the use of condoms, believing they are protected 24,25 . It appears, therefore, that the use of condoms involves socio-cultural issues, which differ among genders, ages, and types of partnerships.…”
mentioning
confidence: 99%
“…Este fato parece estar associado a diversos fatores de vulnerabilidade pessoal e social (SILVA, VARGENS, 2009;BRANDÃO, 2006), tais como: medo do agressor (DATASENADO, 2013); baixo nível de conhecimento sobre direitos ou por descrença no sistema jurídico (na polícia e na Justiça) (DIAS, 2007); falta de condições econômicas para viver sem o companheiro; a preocupação com os filhos e o medo de estarem sujeitas a reações mais violentas pela parte agressora ao se verem denunciadas (BRASIL, 2010;BENFICA, VAZ, DUTRA, 2007).…”
Section: D D D Discussão Iscussão Iscussão Iscussão Iscussãounclassified
“…Various studies have shown that risk in relation to HIV is perceived as a context which is distanced from the individuals (Adefuye, Abiona, Balogun, & Lukobo-Durrell, 2009;Albuquerque, Moço, & Batista, 2010;Camargo, Giacomozzi, Wachelke, & Aguiar, 2010;Giacomozzi & Camargo, 2011;Silva & Vargens, 2009;Sychareun, Thomsen, Chaleunvong, & Faxelid, 2013). Referring directly to the young, studies indicate that they tend to underestimate their risks of infection by HIV and to overestimate the risks of their peers (Anderson, Beutel, & Maughan-Brown, 2007;Mwale, 2008).…”
mentioning
confidence: 99%